Causal Nexus between Stock Price, Demand for Money, Interest Rate, Foreign Institutional Investment, and Exchange Rates in India: A Post Subprime Crisis Analysis - Vyas, Iti; Prasad, Narayan; Mishra, Alok Kumar (UI Scholars Hub, 2011)
This paper makes an attempt to empirically examine the causal nexus between stock price, demand for money, interest rates, foreign institutional investment and exchange rates in India in the post subprime mortgage crisis period. The study employed Granger causality test, Vector Auto Regression and Johansen Maximum Likelihood procedure to examine the short run and long run dynamic interaction among the above mentioned variables for the period January 1993 to May 2009. The major indings of the study are: stock return affects exchange rate return, net foreign institutional investment and growth of demand for money. Growth of demand for money, in turn, affects interest rate. Interest rate is more affected by exchange rate return. Foreign institutional investment also affects interest rate. The co-integration test conirms that there does not exist any long run equilibrium relationship between stock return and exchange rate return